THE XXVII-th INTERNATIONAL CONFERENCE of INVENTICS 'INVENTICA 2023. ' : SCIENCE OF CREATIVITY (Sciendo, 2023)
'INVENTICA 2023'provides an opportunity for all individuals passionate about creativity across all fields to discuss and exchange research ideas.'INVENTICA 2023'is a celebration event dedicated to inventors, creators in technique and art and also, a collaborative platform in a stimulating, innovational, cultural atmosphere, cultivated over the past 50 years by the School of Inventions in Iasi. It aims to showcase, disseminate and promote scientific research findings and cutting-edge technological advancements, while also identifying the progress and current state of the field of creativity. The'INVENTICA 2023'Conference encourages scientific investigation in invention, innovative and inventive products, and brings together researchers interested in the field of invention, innovation and creativity. The primary focus area of the'INVENTICA 2023'Conference include psycho-technical creation, technical creation methods, interdisciplinary research on optimizing human performance, creativity in engineering, the intersection of science and art, and intellectual property. The main purpose of the Conference as a study of creativity is to establish an academic forum for scientific innovation and creativity. The event also offers a valuable opportunity to communicate, network, and share research and innovation outcomes with a broad audience of the general public and users. The 27th Inventica International Conference is scheduled to be held on June 22nd – 23rd 2023 at the Aula Carmen Silva of Technical University “Gheorghe Asachi” in Iasi, Romania. The event is organized by the National Institute of Inventics Iasi at “Gheorghe Asachi” Technical University of Iasi and the Department of Digital Production Systems, Faculty of Machine Manufacturing and Industrial Management. Contact: inventica.conferinta@tuiasi.ro Instruction for Authors Copyright declaration Guidelines for Reviewers The Conference Fee (100 € for paper) includes: admission to all sections and on-line workshops, the volumes of Conference and certificate of attendance. Please submit papers via online submission platform Editorial Manager: Editorial Manager ABSTRACTING & INDEXING Baidu ScholarBayerische StaatsbibliothekBDSBoDBowker Book DataCiandoCNKI Scholar (China National Knowledge Infrastructure)DimensionsEBSCOExLibrisGoogle BooksGoogle ScholarNavigaReadCubeSemantic ScholarTDOne (TDNet)WorldCat (OCLC)X-MOL